In Silico Senyawa Bioaktif Tanaman Obat Indonesia sebagai Inhibitor Xanthine Oxidase melalui Pendekatan Molecular Docking dan ADMET - Shalsa Fitria Zanti; Trisna Kumala Sari (Lembaga Yasin AlSys, 2026)
Xanthine oxidase (XO) plays a role in the formation of uric acid and contributes to hyperuricemia, whereas the use of synthetic inhibitors such as allopurinol is known to have side effects, thus requiring alternatives from the bioactive compounds of medicinal plants. This study aims to evaluate the potential of Dillapiole, Piperine, Hydroxychavicol, Panduratin A, and Isolicoflavonol as XO inhibitors through an in silico approach using molecular docking, as well as Lipinski and ADMET analyses. The results showed that most ligands met the drug-likeness criteria, except for Panduratin A, which had one violation of LogP. All ligands showed negative binding affinity, with Isolicoflavonol having the best affinity (−9.5 kcal/mol), followed by Piperine and Panduratin A. ADMET predictions showed that most ligands had good absorption and were not mutagenic, although some ligands had the potential to interact with CYP450 enzymes. Overall, Isolicoflavonol showed the best potential as an XO inhibitor candidate based on binding affinity and ADMET profile. These findings affirm the potential of medicinal plant bioactive compounds as alternative XO inhibitors, although further in vitro and in vivo testing is still needed for further validation.